EU Commission proposal for joint gas purchasing, price caps and collective allocation of gas: an assessment - Barnes, A (Oxford Institute for Energy Studies, 2022)
The European gas crisis has led to pressure from several EU Member States to put in place wholesale price caps. In October and November 2022, the EU Commission proposed a series of measures including: a wholesale gas price cap; joint purchasing of gas; calculation of a European LNG price benchmark by the European energy regulator, ACER; and default rules for the collective allocation of gas between Member States in the event of an emergency. The paper assesses the various proposals and likely impact on European gas markets.